A Phase 2a dose‐escalation study of the safety, tolerability, pharmacokinetics and haemodynamic effects of BMS‐986231 in hospitalized patients with heart failure with reduced ejection fraction. (5th July 2017) - Tita, Cristina; Gilbert, Edward M.; Van Bakel, Adrian B.; Grzybowski, Jacek; Haas, Garrie J.; Jarrah, Mohammad; Dunlap, Stephanie H.; Gottlieb, Stephen S.; Klapholz, Marc; Patel, Parag C.; Pfister, Roman; Seidler, Tim; et al.
Abstract: Aims: This study was designed to evaluate the safety, tolerability and haemodynamic effects of BMS‐986231, a novel second‐generation nitroxyl donor with potential inotropic, lusitropic and vasodilatory effects in patients hospitalized with decompensated heart failure and reduced ejection fraction (HFrEF). Methods and results: Forty‐six patients hospitalized with decompensated HFrEF were enrolled into four sequential dose‐escalation cohorts in this double‐blind, randomized, placebo‐controlled Phase 2a study. Patients with baseline pulmonary capillary wedge pressure (PCWP) of ≥20 mmHg and a cardiac index of ≤2.5 L/min/m 2 received one 6‐h i.v. infusion of BMS‐986231 (at 3, 5, 7 or 12 µg/kg/min) or placebo. BMS‐986231 produced rapid and sustained reductions in PCWP, as well as consistent reductions in time‐averaged pulmonary arterial systolic pressure, pulmonary arterial diastolic pressure and right atrial pressure. BMS‐986231 increased non‐invasively measured time‐averaged stroke volume index, cardiac index and cardiac power index values, and decreased total peripheral vascular resistance. There was no evidence of increased heart rate, drug‐related arrhythmia or symptomatic hypotension with BMS‐986231. Analyses of adverse events throughout the 30‐day follow‐up did not identify any toxicities specific to BMS‐986231, with the potential exception of infrequent mild‐to‐moderate headaches during infusion. There were no treatment‐related serious adverse events. Conclusions: BMS‐986231 demonstrated a favourable safety and haemodynamic profile in patients hospitalized with advanced heart failure. Based on preclinical data and these study's findings, it is possible that the haemodynamic benefits may be mediated by inotropic and/or lusitropic as well as vasodilatory effects. The therapeutic potential of BMS‐986231 should be further assessed in patients with heart failure.